Violence in Health Institutions: Türkiye Profile - Diğer, Hülya; Bılgın, Rıfat (My University, 2024)
This research focuses on the exposure of healthcare workers to violence. The aim of the research is to examine the issue of violence in health institutions in the context of Turkey and to create a profile of Turkey. The population of the research consists of articles on violence in health in Turkey. The sample of the research consists of 96 articles. The aim of the research is to reveal the general profile of violence in health institutions in Turkey and to propose a health policy to prevent violence. According to the results of the study, the incidents of violence in health institutions in Turkey have increased significantly as of 2012. However, it was determined that most of the violent incidents took place in public hospitals, emergency services and between 08:00-16:00 hours. Among the other results obtained were that physicians were subjected to the highest number of violent incidents, the highest number of violent incidents occurred in Istanbul, and that violent incidents were mostly perpetrated by service recipients.
Keywords: Türkiye; Violence; Health Policy; Violence in Health; Violence Profile